2016
DOI: 10.1007/s12529-016-9548-9
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Addictive Behaviors Among Chinese Adolescents in Hong Kong, Macau, Taipei, Wuhan, and Zhuhai—a First Cross-subculture Assessment

Abstract: Findings suggest that although the study sites share similar Chinese culture, students in the five cities differed from each other with regard to levels of health behaviors. Relative to the broad socioeconomic development, differences in parental monitoring played a significant role in explaining the observed difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In addition, alcohol use is strongly linked to family economic status. [5][6][7] The amount of family income is related to the status of the pocket money that the adolescents can dispose of as they please, so adolescents with high family income will have more pocket money at their disposal to the extent that they can get alcohol quickly when they want to get it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, alcohol use is strongly linked to family economic status. [5][6][7] The amount of family income is related to the status of the pocket money that the adolescents can dispose of as they please, so adolescents with high family income will have more pocket money at their disposal to the extent that they can get alcohol quickly when they want to get it.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, the rate of alcohol use among adolescents was 21.8%, increasing to 41.2% in 2016 2 and 48.09% in 2022. 3 Previous studies have shown that the main risk factors associated with alcohol use among young people include smoking, 4 monthly household income, 5 , 6 , 7 family environment, 8 , 9 intimate partners 9 , access to alcohol, 10 , 11 alcohol expectations, 12 , 13 social norms of alcohol 14 - 16 and health literacy (HL). 17 , 18 In addition, due to inadequate HL, individuals have limited ability to access, understand, interpret, and evaluate drug-related information and low self-management knowledge to make appropriate decisions to prevent or avoid the risk of drinking or to abstain from drinking.…”
Section: Introductionmentioning
confidence: 99%
“…In China, more than 30 million teenagers aged below 17 years old had behavioral and emotional problems, with less than 30% receiving any mental health treatment (World Health Organization [WHO], 2016). Compared to other Chinese cities, Hong Kong adolescents reported higher levels of health-risk behaviors (e.g., smoking, sedentary lifestyle and gambling) compared to their counterparts in Macau, Zhuhai, and Wuhan (Chen et al, 2016). Adolescents with persistent life dissatisfaction and hopelessness are much more likely to engage in risky behaviors and display poor academic performance (Chen et al, 2016).…”
mentioning
confidence: 93%
“…Compared to other Chinese cities, Hong Kong adolescents reported higher levels of health-risk behaviors (e.g., smoking, sedentary lifestyle and gambling) compared to their counterparts in Macau, Zhuhai, and Wuhan (Chen et al, 2016). Adolescents with persistent life dissatisfaction and hopelessness are much more likely to engage in risky behaviors and display poor academic performance (Chen et al, 2016). Besides, early initiation of problematic behaviors is strongly related to later delinquent behaviors (LaBrie, Rodrigues, Schiffamn, & Tawalbeh, 2007).…”
mentioning
confidence: 93%